Analisis Modalitas Tuturan Mahasiswa dalam Kelas Presentasi - Rizka Hayati; Ida Ayu Panuntun (JURNAL LITBANG KOTA PEKALONGAN, 2021)
Modality in semantics can be said as speaker's expression reflected in his or her word choices. This article took modality as the main theme because modality can explain someone's expression or belief about what is being conveyed. The use of modality which shows speaker’s expression can be seen in the classroom presentation class. Each student will have different choice in using modality.  Actually there are types of modality. Those are intentional, epistemic, deontic, and dynamic. This study aimed to explain the types of modality used by students in explaining the material and expressing their opinions during presentations in class. The method used was descriptive qualitative. The data were collected by using observation. After the data were collected, it was  analyzed by using some stage, those were identification, classification, description and interpretation. From the results of the analysis, it can be concluded that the modality used by students in expressing their opinions during presentation class was intentional modality, epistemologi modality, dynamic modality, and deontic modality. Keywords: Modality, types of modality, utterances, classroom presentation